2023
DOI: 10.1007/s00359-023-01633-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stimulus history on directional coding in the monarch butterfly brain

Abstract: The central complex is a brain region in the insect brain that houses a neural network specialized to encode directional information. Directional coding has traditionally been investigated with compass cues that revolve in full rotations and at constant angular velocities around the insect’s head. However, these stimulus conditions do not fully simulate an insect’s sensory perception of compass cues during navigation. In nature, an insect flight is characterized by abrupt changes in moving direction as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Insights into directional coding by central–complex neurons in monarch butterflies are provided by a study of Jerome Beetz and Basil el Jundi (Beetz and el Jundi 2023 ). The authors have analyzed whether and how spatial tuning of central–complex neurons is affected by different stimulus dynamics, as would occur during turning saccades vs. more slower changes in flight direction.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…Insights into directional coding by central–complex neurons in monarch butterflies are provided by a study of Jerome Beetz and Basil el Jundi (Beetz and el Jundi 2023 ). The authors have analyzed whether and how spatial tuning of central–complex neurons is affected by different stimulus dynamics, as would occur during turning saccades vs. more slower changes in flight direction.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…While the compass system is a major focus of monarch butterfly research [41][42][43][44][45][58][59][60][61][62][63], there are only a few behavioural studies that investigate the foraging behaviour [48][49][50][51]. Here, we demonstrated that non-migratory monarch butterflies could relocate rewarding feeders by learning spatial information of visual landmarks.…”
Section: Discussionmentioning
confidence: 86%
“…Central complex functions overlap strongly with the cognitive processes that generate pollen-feeding behaviour in Heliconius butterflies, where a goal (the location of a pollen resource) is identified, learned and memorized [109]. Subsequently, sensory cues during navigation and foraging, such as optic flow, wind direction, polarized light and recognition of visual features, are integrated and compared with the original goal, and path integration allows the foraging route to be faithfully navigated [102,[110][111][112].…”
Section: The Cognitive Circuit Of Mushroom Bodies and Central Complexmentioning
confidence: 99%